2020
DOI: 10.18632/aging.103005
|View full text |Cite
|
Sign up to set email alerts
|

GSG2 (Haspin) promotes development and progression of bladder cancer through targeting KIF15 (Kinase-12)

Abstract: Bladder cancer is the most commonly diagnosed malignant tumor in urological system worldwide. The relationship between GSG2 and bladder cancer has not been demonstrated and remains unclear. In this study, it was demonstrated that GSG2 was up-regulated in bladder cancer tissues compared with the normal tissues and its high expression was correlated with more advanced malignant grade and lower survival rate. Further investigations indicated that the overexpression/knockdown of GSG2 could promote/inhibit prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Many studies showed that KIF15 is high expressed in many human cancer tissues and is associated with poor cancer prognosis 30–32 . In this study, we found that the expression of KIF15 was higher in EC tissues than in normal endometrial tissues, increased KIF15 expression is associated with age, tumor grade and TNM stage positively.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Many studies showed that KIF15 is high expressed in many human cancer tissues and is associated with poor cancer prognosis 30–32 . In this study, we found that the expression of KIF15 was higher in EC tissues than in normal endometrial tissues, increased KIF15 expression is associated with age, tumor grade and TNM stage positively.…”
Section: Discussionsupporting
confidence: 48%
“…22 In recent years, several studies have revealed that KIFs are associated with the occurrence and development of a number of cancers, so that mitotic kinesin has attracted widespread Many studies showed that KIF15 is high expressed in many human cancer tissues and is associated with poor cancer prognosis. [30][31][32] In this study, we found that the expression of KIF15 showed that the deficiency of KIF15 could significantly promote the apoptosis of EC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HASPIN is broadly and highly expressed in various cancers compared with the corresponding non-malignant tissues [ 10 , 11 , 26 ]. A recent study has also demonstrated that among the four breast cancer subtypes, luminal A breast cancer tissues had the lowest HASPIN expression levels, whereas basal-like breast cancer tissues exhibited the highest HASPIN expression [ 12 ].…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that KIF15 can promote the malignant progression of bladder cancer, breast cancer, gastric cancer and other tumors. 28–31 In addition, KIF15 promotes the progression of drug resistance in prostate cancer through the androgen receptor pathway. 32 In particular, a number of studies have reported that KIF15 regulates the malignant progression of tumor cells by activating the MEK-ERK signaling pathway in pancreatic cancer, bladder cancer and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%